2022
DOI: 10.1177/00221678221132718
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Workers in Time of Crisis: A COVID-19 Case Study

Abstract: This article focuses on the lived experiences of those implementing community health worker (CHW) programs during the COVID-19 pandemic. Based in an upper mid-west state, this qualitative case study is bounded by the state-level context and two distinct local case sites—one rural and one urban—and includes the experiences of five CHWs, two program directors, and a state-level administrator. The acute crisis response galvanized the ongoing need for CHWs, not only because they are trusted health messengers, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Nevertheless, in contrast to a study in China, older people had higher odds of being vaccinated with a booster dose in this study [ 28 ]. Furthermore, in our study, advise from community health workers was found to be a key factor driving booster vaccination, corroborating global evidence of their trustworthiness in local communities as credible sources of information, thereby enabling the promotion of COVID-19 vaccination and inhibiting vaccine hesitancy [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, in contrast to a study in China, older people had higher odds of being vaccinated with a booster dose in this study [ 28 ]. Furthermore, in our study, advise from community health workers was found to be a key factor driving booster vaccination, corroborating global evidence of their trustworthiness in local communities as credible sources of information, thereby enabling the promotion of COVID-19 vaccination and inhibiting vaccine hesitancy [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 81%
“…Novel challenges that arose due to the pandemic include an increased need for health and financial services, a rise in domestic violence rates, and the closure of other advocacy agencies. This has been a common finding across recent studies of the COVID-19 pandemic, which found many health workers had to find solutions to the increase in need despite limited resources and continuous systemic racism (Ayanian, 2020; Stevenson et al, 2022; Stewart et al, 2021; Stone et al, 2021). However, the participants of this study stated that their organization’s approach to addressing the increase in need was unique in that they decided to remain open and focused on strengthening partnerships between CHWs and community organizations to ensure client needs were met.…”
Section: Discussionmentioning
confidence: 87%
“…The COVID-19 CARES-ACT funding, which emerged in re-sponse to the pandemic, is due to end despite CHWs' critical role in the public health system. 11 Unless alternative, sustainable funding sources are identified at the state and Federal level, there is a substantial risk that the critical CHW infrastructure, which has been instrumental in supporting individuals with LEP to navigate or ameliorate the SDoH in their lives and in their communities and improve clinical outcomes, may sunset as we speak. A promising piece of legislation was recently introduced into Congress (The Community Health Worker Access Act) that would provide for Medicare reimbursement of community health workers, promotoras, and community health representatives for services to (1) prevent illness, reduce physical or mental disability, and restore an individual to the best possible functional level; and (2) address social needs through education and referrals to health care and community-based organizations, and create an optional Medicaid benefit, incentivized by an enhanced Federal Medical Assistance Percentage (FMAP), to cover preventive services and services to address social needs furnished by community health workers, promotoras, or community health representatives."…”
Section: Interpreters' Role In Mitigating Sdoh and Supporting Improve...mentioning
confidence: 99%
“…Yet, despite the undeniable evidence of CHWs’ impact, funding for the role is tenuous. The COVID-19 CARES-ACT funding, which emerged in response to the pandemic, is due to end despite CHWs’ critical role in the public health system 11 . Unless alternative, sustainable funding sources are identified at the state and Federal level, there is a substantial risk that the critical CHW infrastructure, which has been instrumental in supporting individuals with LEP to navigate or ameliorate the SDoH in their lives and in their communities and improve clinical outcomes, may sunset as we speak.…”
Section: Covid-19’s Role In Exacerbating Health Inequitiesmentioning
confidence: 99%